2023
DOI: 10.1007/s00018-022-04621-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of Cl− permeation through cystic fibrosis transmembrane conductance regulator (CFTR)

Abstract: The recent elucidation of atomistic structures of Cl− channel CFTR provides opportunities for understanding the molecular basis of cystic fibrosis. Despite having been activated through phosphorylation and provided with ATP ligands, several near-atomistic cryo-EM structures of CFTR are in a closed state, as inferred from the lack of a continuous passage through a hydrophobic bottleneck region located in the extracellular portion of the pore. Here, we present repeated, microsecond-long molecular dynamics simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 109 publications
1
12
0
Order By: Relevance
“…We observed very similar conformational homogeneity and stability with another member of the ABC transporter family (58). Along the same lines, MD simulations showed that the closed state with dimerized NBDs is stable over hundreds of nanoseconds (79).…”
Section: Discussionthe Allosteric Mechanism Of Cftrsupporting
confidence: 74%
See 2 more Smart Citations
“…We observed very similar conformational homogeneity and stability with another member of the ABC transporter family (58). Along the same lines, MD simulations showed that the closed state with dimerized NBDs is stable over hundreds of nanoseconds (79).…”
Section: Discussionthe Allosteric Mechanism Of Cftrsupporting
confidence: 74%
“…We observed very similar conformational homogeneity and stability with another member of the ABC transporter family (58). Along the same lines, MD simulations showed that the closed state with dimerized NBDs is stable over hundreds of nanoseconds (79). Taken together, these results strongly argue in favor of an induced-fit mechanism, and against MWC/ensemble-selection/population shift models which assume pre-existence of multiple conformations and a spontaneous dynamic equilibrium between them).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Phosphorylation was achieved by replacing the hydroxyl hydrogen on the serine side chain with phosphite (-PO 3 2- ). The DOPC lipid bilayer (44) was used to simulate the cytoplasmic membrane environment, and in our work, it has been expanded to a system with 1152 lipids and 43425 water molecules. A 20 ns simulation at 310 K has been used to stabilize this expanded system.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the intracellular entrance (38, 39) and the cytosolic vestibule (4246) of the pore were clearly defined in the published structures of CFTR (40, 4749), the exact path of chloride from the inner vestibule to the extracellular space remains unclear. Extensive mapping by mutagenesis (5053), cysteine accessibility (38, 5456), and molecular dynamics (57) has also not allowed unambiguous assignment of the extracellular exit. Furthermore, although many residues have been shown to influence the conductance or relative permeabilities of different anions in CFTR (reviewed in (19, 20, 41)), a specific selectivity filter has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%